2018
DOI: 10.1152/japplphysiol.00043.2018
|View full text |Cite
|
Sign up to set email alerts
|

Development of a polarized pancreatic ductular cell epithelium for physiological studies

Abstract: Pancreatic ductular epithelial cells comprise the majority of duct cells in pancreas, control cystic fibrosis transmembrane conductance regulator (CFTR)-dependent bicarbonate ([Formula: see text]) secretion, but are difficult to grow as a polarized monolayer. Using NIH-3T3-J2 fibroblast feeder cells and a Rho-associated kinase inhibitor, we produced well-differentiated and polarized porcine pancreatic ductular epithelial cells. Cells grown on semipermeable filters at the air-liquid interface developed typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…The conditional reprogramming method is applicable to many epithelial tissues including skin, prostate, lung, breast, kidney, salivary gland and liver cell types and it has recently been extended to neuroendocrine and endocrine tissues. Interestingly, the method seems generally applicable to many mammalian species such as mouse, rat, dog, ferret, horse, and cow [52,53,54,55,56,57]. An important feature is that these cultures can be used for establishing xenografts [12,50] and patient-derived xenograft cell lines [58] and can also be used to generate cell cultures from PDX and organoid cultures.…”
Section: Patient-derived Cancer Models and Crc Are Needed For Precmentioning
confidence: 99%
“…The conditional reprogramming method is applicable to many epithelial tissues including skin, prostate, lung, breast, kidney, salivary gland and liver cell types and it has recently been extended to neuroendocrine and endocrine tissues. Interestingly, the method seems generally applicable to many mammalian species such as mouse, rat, dog, ferret, horse, and cow [52,53,54,55,56,57]. An important feature is that these cultures can be used for establishing xenografts [12,50] and patient-derived xenograft cell lines [58] and can also be used to generate cell cultures from PDX and organoid cultures.…”
Section: Patient-derived Cancer Models and Crc Are Needed For Precmentioning
confidence: 99%
“…Whereas intracellular acidification caused by forskolin administration in HCO 3 /CO 2 − buffered solution was created by CFTR and electrogenic NBC1. In 2018, O'Malley et al reported the establishment of a culture system of differentiated pancreatic ductal epithelial cells in a polarized monolayer [32]. In this 2D air-liquid interface culture system, cells were grown on semipermeable filters and were reported to develop epithelial cell morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The eligibility of CR to immortalize a wide range of epithelial cells of varied origins has been proved by many researches. Primary cells from both normal and pathological tissues can be proliferated under CR conditions ( Table 2 12 , 25 , 69 , 83 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ). Of particular note, not only human tissues but also tissues from other origins such as mouse, horse, dog and fish have been used for CR culture.…”
Section: Cr Applicationsmentioning
confidence: 99%
“… Establishment of in vitro and in vivo models for drug screen and drug target identification 128 PDX tumor tissue (first passage) 3 Pig normal pancreatic tissue (newborn pig pancreata) 1 Pancreatic epithelial cells are expanded under CR conditions and have the characteristics of a ductal epithelium, which can differentiate into functional cells at the gas-liquid interface. A model for studying pancreas physiology and mechanisms of bicarbonate secretion 129 Liver Human liver tissue (freshly resected from patients with cirrhosis, hepatitis C, maple syrup urine disease, or citrullinemia type 1 disease) 11 Primary hepatocytes are grown from 6 out of 11 specimens under CR condition, which are genetically identical with original tissues and retain strong CYP3A4, 1A1 and 2C9 activities. Long term culture of patient-derived primary hepatocytes 130 Human tumor tissue (freshly resected) 20 Primary hepatocellular carcinoma cells continuously expand under CR condition and express tumor-specific marker.…”
Section: Cr Applicationsmentioning
confidence: 99%
See 1 more Smart Citation